PROFIL KUALITAS PEMBELAJARAN IPS DI SEKOLAH MENENGAH PERTAMA DI KABUPATEN TANGGAMUS - Nurdin Nurdin; Pujiati Pujiati; Tedi Rusman (Metafora: Education, Social Sciences and Humanities Journal, 2020)
The Quality of Learning Social Studies Profile In Junior High School in the District Tanggamus. This study aimed to analyze the quality of the learning profile of social studies in Junior High School in Kota Agung Tanggamus. Research subjects include the entire social studies teacher and junior high school students in the Kota Agung Tanggamus the academic year 2014/2015. The study includes profiles Object learning social studies in junior high quality of the Kota Agung, Tanggamus. The collection of data through observation, interviews and questionnaires. Data were analyzed using descriptive analysis. The results showed that the profile of learning quality of teachers in the social studies category Tanggamus already good, it can be seen from several indicators of educational qualifications, the ability to transform knowledge, the ability to develop and disseminate science and technology, the ability to plan, implement and evaluate learning, the ability to describe the model thinking on students, the use of methods and strategies, ability to create a culture of positive thinking, collaborative learning, motivate students to become teachers, foster critical thinking, teachers act as agents of change, teachers siding with the truth and is active in community activities.